Navigating Adolescence with a Chronic Health Condition: A Perspective on the Psychological Effects of HAIR-AN Syndrome on Adolescent Girls - Kimberly K. McClanahan; Hatim A. Omar (The Scientific World Journal)
HAIR-AN syndrome is a subphenotype of polycystic ovary syndrome and is characterized by acne, obesity, hirsutism, and acanthosis nigricans. It usually manifests in early adolescence, a time of significant developmental change in females across physical, cognitive, social, and emotional domains. We contend that adolescent development for females is difficult, even in the best of circumstances, and having a chronic health condition, like HAIR-AN syndrome, will likely impact the afflicted individuals development and psychological well-being. While many researchers have discussed the long-term health effects of HAIR-AN and similar disorders, little has been written about the potential psychological sequelae of HAIR-AN on the adolescent girl. We discuss the normal developmental sequence for adolescent girls across early, middle, and late adolescence; discuss common mental health problems that adolescents experience; define HAIR-AN syndrome and its clinical manifestations; and discuss its likely psychological impact on adolescent girls. We also make suggestions for future clinical interventions and research in the area of HAIR-AN syndrome and its psychological sequelae.